Bezlotoxumab for Prevention of Recurrent Clostridium difficile Infection in Patients at Increased Risk for Recurrence. (10th March 2018) - Gerding, Dale N; Kelly, Ciaran P; Rahav, Galia; Lee, Christine; Dubberke, Erik R; Kumar, Princy N; Yacyshyn, Bruce; Kao, Dina; Eves, Karen; Ellison, Misoo C; Hanson, Mary E; Guris, Dalya; et al.
Abstract: Background: Bezlotoxumab is a human monoclonal antibody against Clostridium difficile toxin B indicated to prevent C. difficile infection (CDI) recurrence (rCDI) in adults at high risk for rCDI. This post hoc analysis of pooled monocolonal antibodies for C. difficile therapy (MODIFY) I/II data assessed bezlotoxumab efficacy in participants with characteristics associated with increased risk for rCDI. Methods: The analysis population was the modified intent-to-treat population who received bezlotoxumab or placebo (n = 1554) by risk factors for rCDI that were prespecified in the statistical analysis plan: age ≥65 years, history of CDI, compromised immunity, severe CDI, and ribotype 027/078/244. The proportion of participants with rCDI in 12 weeks, fecal microbiota transplant procedures, 30-day all cause and CDI-associated hospital readmissions, and mortality at 30 and 90 days after randomization were presented. Results: The majority of enrolled participants (75.6%) had ≥1 risk factor; these participants were older and a higher proportion had comorbidities compared with participants with no risk factors. The proportion of placebo participants who experienced rCDI exceeded 30% for each risk factor compared with 20.9% among those without a risk factor, and the rCDI rate increased with the number of risk factors (1 risk factor: 31.3%; ≥3 risk factors: 46.1%). Bezlotoxumab reduced rCDI, fecal microbiota transplants, and CDI-associated 30-day readmissions in participants with risk factors for rCDI. Conclusions: The risk factors prespecified in the MODIFY statistical analysis plan are appropriate to identify patients at high risk for rCDI. While participants with ≥3 risk factors had the greatest reduction of rCDI with bezlotoxumab, those with 1 or 2 risk factors may also benefit. Clinical Trials Registration: NCT01241552 (MODIFY I) and NCT01513239 (MODIFY II). Abstract : Subgroup analyses from MODIFY confirmed that prior Clostridium difficile infection (CDI), age ≥65 years, infection with 027/078/244 strain, compromised immunity, and severe CDI are risk factors for recurrent CDI. Bezlotoxumab reduced CDI recurrence in participants with ≥1 risk factor compared with placebo.